Hyaluronic Acid Injections as Nonsurgical Alternative in case of Delayed Diagnosis of Malar Arch Fracture: Case Report and Literature Review - Raffaele Rauso; Giorgio Lo Giudice; Nicola Zerbinati; Gianpaolo Tartaro (Case Reports in Surgery)
Background. In this article, we describe a nonsurgical approach based on hyaluronic acid filler injection to restore the facial features of a delayed diagnosis of malar fracture. We analyze the differences between surgical and nonsurgical solution: in case of early detection, the surgical approach is the gold standard of treatment. However, in cases of delayed facial fracture diagnosis without functional impairment, nonsurgical procedures could be considered an alternative tool as we show in the present case report. Aims. The aim of this study is to underline the importance of a complete aesthetic restoration in patients treated for noncosmetic purposes. Patients/Methods. We present a case of a 26-year-old male patient with a delayed diagnosis of malar fracture without functional impairment that was treated with hyaluronic acid (HA) filler injections. Results. The patient was followed up for 1 year showing stable results for the first 8 months; at the 12-month follow-up, a touch-up was suggested due to partial resorption of the filler. Conclusion. This is the first case describing a facial fracture treated with HA injections for only recontouring purposes. We assess that nonsurgical cosmetic procedures could be considered a “new” tool in the process of facial rehabilitation but only when functional problems are not associated with facial trauma.